2018
DOI: 10.3390/nano8110897
|View full text |Cite
|
Sign up to set email alerts
|

A Compact and Smooth CH3NH3PbI3 Film: Investigation of Solvent Sorts and Concentrations of CH3NH3I towards Highly Efficient Perovskite Solar Cells

Abstract: Four solvents (isopropanol (IPA), n-butyl alcohol (NBA), n-amyl alcohol (NAA), and n-hexyl alcohol (NHA)) were investigated to prepare CH3NH3I (methylammonium iodide, MAI) solutions to transform PbI2 film into CH3NH3PbI3 (MAPbI3) film. It was found that the morphology of the perovskite MAPbI3 film was not only affected by the chain of the solvent molecule, but also by the concentration of MAI. The use of solvents with a long alkyl chain (NAA and NHA) allowed the MAPbI3 to grow via an in situ transformation ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…To improve energy conversion efficiency, zero-dimensional TiO 2 nanoparticles have been used as ETMs in perovskite solar cells and dye-sensitized solar cells due to the presence of a large band gap semiconductor and a large surface area [9,26,27,28,29]. Recently, perovskite stability, Au-free back electrodes, Pb-free sensitizers, various additives, additive-free HTMs, large-area modules, and Indium tin oxide (ITO)/Fluorine-doped tin oxide (FTO)-free devices have been studied substantially [1,3,5,30,31,32,33,34,35]. The structure of perovskite is ABX 3 , which is very weak under humidity, heat, light, and oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…To improve energy conversion efficiency, zero-dimensional TiO 2 nanoparticles have been used as ETMs in perovskite solar cells and dye-sensitized solar cells due to the presence of a large band gap semiconductor and a large surface area [9,26,27,28,29]. Recently, perovskite stability, Au-free back electrodes, Pb-free sensitizers, various additives, additive-free HTMs, large-area modules, and Indium tin oxide (ITO)/Fluorine-doped tin oxide (FTO)-free devices have been studied substantially [1,3,5,30,31,32,33,34,35]. The structure of perovskite is ABX 3 , which is very weak under humidity, heat, light, and oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Power conversion efficiency (PCE) enhancement was attributed to the cascade effect, facilitating electron transport from the active layer to ITO bottom electrode, as well as the morphology improvement between the interfaces of the binary blend components. The last article of this section is by Chen et al [25], who examined the effect of solvent polarity, as well as the concentration of the precursor methylammonium iodide (MAI) on the morphology of MAPbI 3 perovskite thin films. They found that better coverage and compactness were achieved according to the longer alkyl chain of the solvent (lower polarity), although the film's roughness was higher.…”
mentioning
confidence: 99%